2010
DOI: 10.4269/ajtmh.2010.10-0132
|View full text |Cite
|
Sign up to set email alerts
|

Climate, Landscape, and the Risk of Orbivirus Exposure in Cattle in Illinois and Western Indiana

Abstract: Abstract. Climate and environmental data were used to estimate the risk of testing positive for antibodies to bluetongue (BTV) and epizootic hemorrhagic disease viruses (EHDV) in cattle in Illinois and western Indiana over three transmission seasons (2000)(2001)(2002). The risks of BTV and EHDV seropositivity were positively associated with temperature during every year of the study. The EHDV seropositivity was also positively associated with forest patchiness in two of the years. During 2002, a year with unus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…There have been few comprehensive analyses of the drivers of disease outbreaks due to EHDV and BTV in the NE and MW US. In cattle in Illinois, BTV and EHDV antibody prevalences were positively associated with temperature and with EHDV, forest patchiness (Boyer et al 2010). Using the Virginia subset (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) of the same HD data set that we used in the present study, Sleeman et al (2009) reported direct correlations between HD incidence and average temperature for winter, early summer, and late summer, and an inverse relationship with June precipitation.…”
Section: Discussionmentioning
confidence: 96%
“…There have been few comprehensive analyses of the drivers of disease outbreaks due to EHDV and BTV in the NE and MW US. In cattle in Illinois, BTV and EHDV antibody prevalences were positively associated with temperature and with EHDV, forest patchiness (Boyer et al 2010). Using the Virginia subset (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) of the same HD data set that we used in the present study, Sleeman et al (2009) reported direct correlations between HD incidence and average temperature for winter, early summer, and late summer, and an inverse relationship with June precipitation.…”
Section: Discussionmentioning
confidence: 96%
“…The factors underlying this association were not investigated, but likely relate to WTD habitat utilization and larval development sites for Culicoides species. Other studies have found significant clustering, or patchiness of infection, or outbreaks (Boyer et al 2010, Xu et al 2012). In a 3-year study by Boyer et al (2010), temperature was associated with EHDV and BTV seropositivity in cattle during all 3 years of the study, although there were differing spatial distributions between viruses.…”
Section: Fig 4 United States Distribution Of Hemorrhagic Disease (Ementioning
confidence: 95%
“…Other studies have found significant clustering, or patchiness of infection, or outbreaks (Boyer et al 2010, Xu et al 2012). In a 3-year study by Boyer et al (2010), temperature was associated with EHDV and BTV seropositivity in cattle during all 3 years of the study, although there were differing spatial distributions between viruses. Furthermore, forest patchiness was associated with EHDV seropositivity in cattle for two of three seasons, and heavy spring rainfall was hypothesized to play a role in the lack of association during the third year, which is supported by other studies (Sleeman et al 2009).…”
Section: Fig 4 United States Distribution Of Hemorrhagic Disease (Ementioning
confidence: 95%
See 1 more Smart Citation
“…In North America, C. sonorensis is considered to be the predominant vector for both viruses, although it is recognised that other vectors, for example C. mohave, might be regionally important (82,83,84). Interestingly, however, EHDV infection extends into the Canadian states of Saskatchewan and Alberta, whereas BTV does not (12,82,85,86). In contrast, whereas BTV has recently invaded extensive portions of Europe, EHDV has not and Europe is currently free of EHDV infection despite the presence of the virus on the southern and eastern rims of the Mediterranean Basin (4).…”
Section: Epidemiology and Modes Of Transmissionmentioning
confidence: 99%